The Dominican Republic : Stabilization, Structural Reform, and Economic Growth - Cardoso, Jaime (Occasional Papers; Occasional Paper ;, 2002)
This paper summarizes the authorities' stabilization efforts, how these efforts were subsequently reinforced by certain key structural reforms, and other related developments that help explain the remarkable performance of the Dominican Republic's economy in the 1990s during which the country achieved one of the highest output growth rates in Latin America, combined with low inflation, and a much improved external debt profile. The authorities often resorted to external arrears as a means of financing the external current account deficits of the 1980s. Although rescheduling agreements were reached with the international banking community and with the Paris Club of official creditors in the mid-1980s, they met with limited success until the authorities embarked on their stabilization program of the early 1990s. Large and persistent fiscal deficits represented a significant burden for monetary policy. Although at the beginning of the decade more than half of the public deficit was financed by foreign loans, episodes of default on external and domestic government debt led to a progressive drying up of these sources of financing.